COMPOSITIONAL CHANGES IN A FUMAROLIC FIELD, VULCANO ISLAND, ITALY: A STATISTICAL CASE STUDY - Buccianti A.; Tassi F.; Vaselli O. (My University, 2006)
The identification of compositional changes in fumarolic gases of active volcanic areas is one of the most important objectives in monitoring programmes. Together with information from seismic data and deformation, it provides key data to the formulation and management of emergency plans for populations living near active volcanoes. Chemical data obtained from different fumaroles collected at Vulcano Island (Sicily, southern Italy) between 2000 and 2004 have been analysed statistically. The methodology has identified parameters able to elucidate the structure of the complex fumarolic field of Vulcano in the investigated span of time, notwithstanding the high data variability. The southern portion of the Tyrrhenian Sea was affected by an earthquake (M = 5.8, 40 km NE of Palermo) in December 2002. Abrupt outgassing on the island of Panarea occurred in November 2002 and Stromboli was significantly active from December 2002 to July 2003. The great geological instability of the area is thought to have had an influence on the variability shown by the data. The time-dependent variations in the components of the data have been investigated using logratios. The H2O-HCl-SO2 subcomposition, for a limited set of fumaroles, has been used to check for log-contrast principal components to be considered as a monitoring tool of volcanic activity. Results obtained indicate that the compositional changes are a complex function of time, chemistry, temperature and space. ANOVA (analysis of variance) of log-ratios for which there is no time dependence has elucidated components subject to significant spatial variations across the fumarole field, due to changes in redox conditions, and components dominated by random variations. © The Geological Society of London 2006.